High methylmercury formation in ponds fueled by fresh humic and algal derived organic matter. (10th November 2017) - Herrero Ortega, Sonia; Catalán, Núria; Björn, Erik; Gröntoft, Hannes; Hilmarsson, Torfi Geir; Bertilsson, Stefan; Wu, Pianpian; Bishop, Kevin; Levanoni, Oded; Bravo, Andrea G.
Abstract: Neurotoxic methylmercury causes adverse effects to ecosystem viability and human health. Previous studies have revealed that ponding alters natural organic matter (NOM) composition and increase methylmercury concentrations in rivers, especially in the first years after flooding. Here, we investigate the influence of NOM composition (i.e., sources and degradation status) on mercury methylation rate constants in nine boreal beaver ponds of different ages across Sweden. We show that increased methylmercury concentrations in surface waters is a consequence of enhanced mercury methylation in the pond sediments. Moreover, our results reveal that during the first years after the initial flooding, mercury methylation rates are fueled by the amount of fresh humic substances released from the flooded soils and by an increased production of algal‐derived NOM triggered by enhanced nutrient availability. Our findings indicate that impoundment‐induced changes in NOM composition control mercury methylation processes, causing the raise in MeHg levels in ponds.